Contributions of changes in climatology and perturbation and the resulting nonlinearity to regional climate change - Sachiho A. Adachi (Nature Portfolio, 2017)
Changes in climatology and perturbation will lead to different impacts on regional climate change, but their effect remains a subject of debate. Here the authors develop a new downscaling procedure that reveals the importance of both changes on the regional climate and examines their nonlinear effect.